Why Diabetes Worsens Patient Prognosis: A Literature Review of Cardiovascular and Renal Complications - Magdalena Rafałowicz; Adam Rafałowicz; Urszula, Justyna Wojciechowska; Jakub Mierzejewski (Quality in Sport)
Background. Diabetes is considered a serious chronic metabolic disease due to its increasing prevalence worldwide. The main factor worsening the prognosis of patients is cardiovascular complications, which are the main factors of morbidity and mortality in diabetes.